Determinants of quality of life following resection of skull base tumors: a systematic review - Veronika Sperl; Thomas Rhomberg; Thomas Kretschmer (Frontiers in Oncology)
BackgroundSkull base tumors represent a small subset of intracranial neoplasm. Due to their proximity to critical neurovascular structures, their resection often leads to morbidity. As a result, surgical interventions can exacerbate symptoms or cause new deficits, thereby impacting the patients’ perceived quality of life (QoL). The factors influencing QoL in patients with skull base tumors remain underexplored. This systematic review aims to synthesize current research on QoL outcomes and identify potential factors influencing QoL in these patients.MethodsA systematic literature review was conducted in PubMed using the keywords “Skull Base” AND “Quality of Life.” A total of 815 studies published up to January 31, 2024, were screened. After abstract review, 656 studies were excluded, and 159 studies underwent full-text review. The wide variability in study methodologies and utilized QoL instruments made only a descriptive comparison possible.ResultsIn total, 113 studies were systematically reviewed. Publications focusing on the same tumor type or localization were compared. The majority of studies addressed tumors of the anterior skull base, with pituitary adenomas, meningiomas and vestibular schwannomas being the most commonly represented. The impact of surgery on QoL is often underestimated by caregivers and has a more profound effect on patients than expected by surgeons. A transient decline in QoL after surgery was observed across almost all studies regardless of localization and entity. Factors influencing QoL included age, gender, tumor localization, surgical approach, tumor type, extent of resection, preoperative clinical status and neurological deficits. Radiotherapy and recurrent surgeries were predictors of poorer QoL. Early psychological intervention in complex tumors appears to enhance QoL. Some successful sealing techniques, such as nasoseptal flaps and lumbar drains, affected QoL. However, variability in study methodologies reduced the validity of the findings.ConclusionThis review highlights the significant impact of skull base tumor surgery on patients’ QoL. Given the major oncological and surgical challenges presented by skull base tumors, their treatment significantly affects QoL, and gross total resection (GTR) should not always be the primary goal. Additionally, recognizing and addressing the modifiable and non-modifiable factors influencing QoL is crucial for improving patient outcomes and providing personalized care.